Semiotic Communication: An Approach Of Understanding A Meaning In Communication - Ibrahim, Ibrahim; Sulaiman, Sulaiman (UIR Press, 2020)
In interpreting communication, we are often trapped in symbols and a set of signs that are used. This is due to our simple assumption that tends assume on symbols or signs that stand alone in representing meaning. We forget that symbols or signs, as well as meaning are complex. Though they are not stand alone. They are representation of the many factors that influence them, including the knowledge and culture of their participants. In media, the meaning of symbols or signs that used to convey news is very dependent on the ideology of the media and the whole organization that manages the media. Even the